Chromosomal location of genes encoding for resistance to septoria tritici blotch (Mycosphaerella graminicola) in substitution lines of wheat - Simón, María Rosa (2005)
Chromosomal location of resistance to Mycosphaerella graminicola was studied in substitution lines of resistant Triticum genotypes into the (susceptible) cultivar Chinese Spring (T. aestivum). (Moderately) resistant genotypes for which substitution lines were available were tested in a first screening. We selected a synthetic hexaploid wheat (Synthetic 6x; T. dicoccoides × T. tauschii), T. spelta and the wheat (T. aestivum) cultivars Cheyenne and Cappelle-Desprez. In a second screening the most suitable Argentinian isolates were identified. We decided to use the isolate IPO 92067 (all sets of substitution lines), IPO 93014 (substitution lines of Synthetic 6x, Cappelle-Desprez and T. spelta) and IPO 92064 (substitution lines of Cheyenne). In the final experiments, substitution lines of the selected genotypes into Chinese Spring were grown in two different environments and inoculated with the selected isolates at the seedling stage (lines of all four selected genotypes) or the adult stage (lines of Synthetic 6x and Cheyenne). Resistance was expressed as (reduction in) necrosis percentage or pycnidial coverage percentage; the two measures were highly (linearly) correlated. When tested in the seedling stage, all chromosomes seemed to carry genes effective against M. graminicola. Many genes were effective against only one isolate or in only one environment or their effects only showed in one resistance parameter. Often these effects were minor. Only chromosome 7D of Synthetic 6x was found with a major effect against both isolates tested. When tested in the adult stage, all lines but the one carrying chromosome 4B from the resistant parent seemed to show genes effective against M. graminicola. The line carrying chromosome 7D from Synthetic 6x showed a level of resistance similar to the resistant parent for isolate IPO 92067, but not for isolate IPO 93014. Major genes, effective against both isolates, were also found on chromosomes 5A and 5D from Synthetic 6x. Lines carrying chromosome 1B, 5D or 6D from Cheyenne showed major effects against isolate IPO 92064. For both necrosis percentage and pycnidial coverage percentage, highly significant linear correlations were found between resistance in the seedling stage and resistance in the adult stage. However, the variance accounted for was only small (20-24%; n = 184).